Lugares e tempos em narrativas de uma educação ambiental pós-colonial no Sítio dos Crioulos - Jerônimo Monteiro - E.S. - Maulin, Gilfredo Carrasco (2013)
Discussion and analysis of the many temporalities and spaces of identity in the Site of Creoles, maroon community of the city of Jerônimo Monteiro, south of Espirito Santo. The goal is to understand the forms of knowledge produced by the community, as well as its connections in the time-space relationship in the glare of what we can call a local environmental education, considering the different ways of life that exist there, as well as the uses and appropriations of nature and identity processes. The uses of narrative through open interviews and participant observation methodology comprise the experiences of the practiced place. Research that engenders environmental knowledge - translation with the doings of the community: the playful, the plantation and the sacred are spacetimes that allow thinking about radicalization and annunciation of social and cultural practices as synonyms of the completion of the environment as narratives denoting stories that emerge from the rulling and instrumental silencing of modernity, which reduced the so-called traditional communities to the conformation of non-scientific knowledge endowed with irrationalities. This research aims to understand how it is possible to think of an environmental education from the inside out, where the researcher and researched relationship is established as a point of approach and conflict of the sociocultural dynamics established by this encounter, which brings us closer to a postcolonial environmental education which comes from the narratives and experiences in the convergence of local differences and of what is produced and translated with them. This paper examines these approach and distancing processes that cause other translations on the natureculture of ourselves, individuals and society.